Sinopse de poaceae das formações campestres do Parque Estadual Do Guartelá, Paraná, Brasil - Souza, Tainã de (2017)
Considered one of the greatest families among the angiosperms and with great ecological amplitude, Poaceae species can be found both in forest as well as in campestre formations. The goal of the present study was to perform the first floristic survey of Poaceae in one of the last remnants native vegetation of campestre formations in Paraná, the Guartelá State Park (GSP), besides elaborate dichotomous keys in order to identify the genera and species. The survey was carried out based on field collecting and database search. The dichotomous keys were elaborated using qualitative and quantitative characters of the genera and species. In the GSP, the family is represented by 54 species belonging to 29 genera, Paspalum L. (8 spp.), Andropogon L. (5 spp.) and Eragrostis Wolf (4 spp.) being the ones that presented the greater number of species. The number of species cited previously to the GSP increased in 29 names and from the total (54) five are considered exotic, five endemics to Brazil and two are categorized as least concern to conservation, occurring both in dry and wet areas, highlighting the importance of the GSP microenvironments conservation. Information regarding the distribution, habitat and species conservation are presented.